1976
DOI: 10.1021/ic50165a059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic strength on the activation parameters of fast electron-transfer reactions

Abstract: The activation parameters of the V(II)-Fe(III) and U(III)-Fe(III) reactions were determined as a function of ionic strength in perchlorate media. Contrary to expectations, the values of AS* for these reactions were found to be independent of ionic strength, the changes in rate constant being reflected exclusively in the values of AH*. Plausible explanations for these observations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Contrary to expectation, the rate increase with increasing ionic strength is reflected almost entirely in a decreased enthalpy of activation. This conclusion has previously been reached on the basis of studies of the aquo-ion systems alone (22). However the aquo-ion exchanges cannot be studied at low ionic strengths since ^ 0.1 M acid is required to suppress the hydrolysis of the +3 ions.…”
Section: Ah* » -Rt/2 (20) Transmentioning
confidence: 81%
See 1 more Smart Citation
“…Contrary to expectation, the rate increase with increasing ionic strength is reflected almost entirely in a decreased enthalpy of activation. This conclusion has previously been reached on the basis of studies of the aquo-ion systems alone (22). However the aquo-ion exchanges cannot be studied at low ionic strengths since ^ 0.1 M acid is required to suppress the hydrolysis of the +3 ions.…”
Section: Ah* » -Rt/2 (20) Transmentioning
confidence: 81%
“…In Figure 2 the predicted ionic strength dependence of the entropy of activation is compared with experimental data for electron-transfer reactions for which AS « 0. The data include several aquo-ion systems (22) and the exchange reaction of a ruthenium amine couple (23). It will be seen that the entropies do not increase with ionic strength as predicted-instead they are essentially independent of ionic strength.…”
Section: Ah* » -Rt/2 (20) Transmentioning
confidence: 99%
“…3 should be some 140% larger than corresponding values from the set shown as triangles, whereas the actual difference is only about 40%. Indeed, several authors have reported that ionic strength effects on electron exchange reactions between two ions of like charge are anomalous or even undetectable at the relatively high electrolyte concentrations dictated by practical considerations in experiments such as those described here (4,(14)(15)(16)(17). This phenomenon appears to be due, at least in part, to the formation of relatively unreactive ion pairs with the counterion, as this would act in opposition to the accelerating effect of ionic strength (14,(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that such a treatment of the ionic-strength dependence of ∆S ‡ is not satisfactory. In particular, a 80 J mol -1 K -1 increase of the activation entropy is predicted when the ionic strength increases from I = 0 to 1·0 M for a reaction in water involving two tripositive ions separated by 500 pm in the activated complex [102], but the experimental data show that ∆S ‡ is independent of I [17,102]. The use of the Born-type electrostatic continuum contribution, ∆G out *, to the freeenergy of activation of redox reactions of ions in solution was critized by Khan and Zhou [103].…”
Section: +/2+mentioning
confidence: 95%
“…[3], measurement in media with ionic strengths greater than 0·1 M should affect the large majority of the calculated rates by less than a factor of 20. It is appropriate to mention here that only a factor of 5 increase in the rate constant is observed when I is increased from 0·1 to 1·0 M, and that the entropy of activation is essentially independent of the ionic strength, revealing the complete failure of the predictions of models based on the effect of Coulombic interactions in the vicinity of charged ions immersed in a dielectric continuum [17,102]. Henceforward, with the exception of the Fe(CN) 6 3-/Co(phen) 3 2+ couple, we will neglect the influence of the work terms in the reaction rates and look elsewhere for the reason for the tendency of relative Marcus theory to overestimate the cross-reaction rates.…”
Section: Figure 10 Electron Cross-reaction Rates Of Transition-metalmentioning
confidence: 99%